Revisiting the Greening of Prime-Time Television Soap Operas. Issue 1 (February 2013) - van Vuuren, Kitty; Ward, Susan; Coyle, Rebecca
In 1990, Christopher Rissel and William Douglas commenced a study of the depiction of environmental issues and behaviours on Australian prime-time television drama series. Their findings were discussed in an issue of Media International Australia in 1993. This article reports on a 2011–12 study that replicated key aspects of Rissel and Douglas's research. A collaborative research team focused on two long-running and high-rating Australian soap operas – Neighbours and Home and Away – recorded from June to August 2011. Using content analysis, the researchers investigated the frequency, attitudes to and role models for the representation of environmental issues and behaviours. This article discusses the findings in terms of contemporary television practices and industry, as well as the study's methodology.